Why Leaders Fail in Introducing Values-Based Leadership? An Elaboration of Feasible Steps, Challenges, and Suggestions for Practitioners - Viinamäki, Olli-Pekka (Canadian Center of Science and Education (CCSE), 2012)
The recent debate on modernizing leadership and organizations has placed a strong emphasis on values and ethics. This article elaborates on the benefits and challenges in the integration of values into leadership actions, most notably in regards to appraisals of Values-Based Leadership (VBL). The article contributes to a more specified understanding of the interrelation of stages in the VBL and the pitfalls in each step. A key argument is that if the critical issues and challenges in the introduction of the VBL are not identified, this would lead to unintended consequences in organizations, such as insignificant value-statements, inappropriate use of values, and illegitimate leadership practice. Contrary to many developmental suggestions of more virtuous and ethical or values-based leadership qualities, this article proposes leadership actions for leaders to undertake an effective, sound, and sustainablevalues-based leadership practices.
Keywords: values-based leadership; organizational values; ethics; values (cultural objects); fi=Julkisjohtaminen|en=Public Management|